Student’s sleep. Achievements and challenges for health promoting universities - Soto Bustamante, Rocío (2024)
The aim of this paper is to describe and reflect on the sleep problem in the university population, even before the pandemic, as well as to present a review of the main interventions to promote sleep in universities. In this context, we describe how poor sleep quality is related to different psychological variables of interest for mental health, and we emphasize its consequences on the performance and wellbeing of students. Likewise, a review of the main intervention experiences from the Health Promoting Universities movement is made, discussing the achievements and proposing recommendations to face the challenges posed by the promotion of healthy sleep. Among the recommendations, the academy is asked to take on the challenge of systematically generating evidence to carry out sustainable interventions that have an impact on the university community.